Average demands and most demanding passages of national-level female soccer matches: do small- and large-sided games replicate match demands? - Savolainen, E. H. J.; Vänttinen, T.; Peltonen, J.; Ihalainen, J. K.; Walker, S. (Frontiers in Sports and Active Living, 2023)
Introduction This study aims to (1) determine the average and most demanding passage (MDP) load of national-level female soccer matches and (2) evaluate the relationship between average and MDP load during small-sided games (SSGs), large-sided games (LSGs), and matches. Methods A total of 37 national-level female soccer players from a single club senior team and the U18 team participated. The average and 1-, 3-, and 5-min MDP external (total, high-speed, and very-high-speed running distances, acceleration and deceleration distances, average metabolic power, and high-metabolic load distance) and internal loads (average heart rate, rate of perceived exertion) of the 29 league matches, ten 4 vs. 4 + goalkeepers SSGs, and six 8 vs. 8 + goalkeepers LSGs were analyzed by the Polar Team Pro player tracking system. Results In matches, the external load variables during 1-, 3-, and 5-min MDPs were 167%–1,165%, 135%–504%, and 126%–359%, of match average values, respectively. In LSGs, all external load variables reached higher average values compared with those during matches, except for the very-high-speed running distance; however, no variable reached higher values of 1-min MDP compared with those during the matches. In SSGs, the average acceleration and deceleration distances were higher compared with those during the matches. Discussion The findings from the present study suggest that LSGs and SSGs can be used to overload the average values of the selected external load variables compared with those during the matches; however, other training options must be explored to overload 1-min match MDPs.